Loss of ARF5 impairs recovery after lysosomal damage - Iwaniec, Martyna O.; Bott, Christopher J.; Casanova, James E. (Frontiers in Molecular Biosciences, 2025)
Lysosomal dysfunction is a defining feature of aging and neurodegenerative diseases, where lysosomal membrane permeabilization and release of its contents can trigger cellular death pathways. To counteract this, cells rely on lysosomal quality control mechanisms, many of which depend on lipid delivery to repair damaged membranes. However, the regulatory pathways governing this process remain unclear. In this study, we investigated whether canonical ARF GTPases, best known for their roles in Golgi and endosomal vesicular trafficking, are recruited to damaged lysosomes and contribute to their repair. Using LysoIP-based lysosome isolation, super-resolution immunofluorescence imaging, and functional assays in HeLa and HEK293 cells, we found that ARF1, ARF5, and ARF6 localize to lysosomal membranes following L-leucyl-L-leucine methyl ester (LLOME)-induced permeabilization. While loss of ARF6 did not impair recovery, ARF5 depletion resulted in a nearly complete block of lysosomal repair. These findings identify ARF proteins as early responders to lysosomal damage and suggest isoform-specific roles in coordinating the pathways of lysosomal quality control.